Rozważania nad zagadnieniami efektywności organizacji w systemie ochrony zdrowia - Frączkiewicz-Wronka, Aldona; Austin, Agata (Considerations on Questions About Effectiveness of an Organization in the Health Care System, 2008)
It could be stated that - as far as the concept of effectiveness is generally understood - an attempt of implementing it in the health care system evokes many difficulties. It is not easy to evaluate the benefits of a well-organized health care system to the country. In the response to many questions about that topic the author of this article took the effort to create a concept of an organization's effectiveness in the health care field.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 36, s. 13-24